The Household Food Insecurity Amidst the Covid-19 Pandemic in Indonesia - Anwar, Muhammad; Nasrudin, Rus'an (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
The Coronavirus Disease 2019 (Covid-19) pandemic creates both the demand and supply shocks problem that may affect the households’ food insecurity.  Among mechanisms, it ranges from the limited physical access to food due to social distancing to the drop in economic access to food due to (partial) lockdown. This study aims to lay out an early warning assessment of the food security situation in Indonesia amidst the Covid-19 outbreak. We use the cartogram analysis which visualize the geographical features throughout the Indonesia archipelago, both in the small and big island setting. The analysis involves the use of both the simple score and latent measurement-based scale of the Rasch model for the food insecurity based on the Susenas data from 2017-2019. The finding reveals that there existed a variation of the household proportion that suffers from severe food insecurity across the Indonesia archipelago. The more eastern the island, the worse the measure is. Papua and Maluku suffer more from such condition compared to the other big islands.  As the government has applied any containment measures, the surge in Covid-19 cases may potentially worsen both the existing households under severe food insecurity and even create new households under such conditions.